Effect Dance On Cardiorespiratory Fitness Of Adults :Literature Review - Natalia, Ike; Rahayu, Umi Budi; Mutalazimah (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Background: Low of physical activity in adulthood increases the risk of cardiovascular disease, obesity, metabolic disorders such as diabetes mellitus, which can ultimately reduce a person's quality of life. According to WHO adults should at least do 150 minutes of exercise or at least 75 minutes/week. Dance is a form of physical activity that can be recommended as an alternative intervention to increase Vo2max. Objective: a literature review was conducted to identify dance as an alternative intervention to improve cardiorespiratory fitness. Methods: article search using Scopus database, PubMed, Science Direct, and Cochrane with inclusion criteria research subject age adults 18-64 years research type pilot study, randomized control trial, observational study published in the last 10 years in English and Indonesian. Results: 35 articles were found according to keywords , there were 4 articles that met the inclusion criteria and were selected for review. The highest increase in cardiorespiratory Fitness with V02max indicator in Aeribic Exercise Training intervention (F (1,14) = 20.23, p < .01) and MAP (F (1,14) = 29.90, p < .001), the Brazilian zamba pre 31.2.2.7 post 37.3.5, the Aerobic Exercise Dance pre 23.66.3.03 post 28.59.4.92, the Greek Traditional Dance 35.95.4.3 post 38.91.3. Conclusion: Dance can be used as an alternative intervention to improve cardiorespiratory fitness with indicators of increased Vo2 Max.